Utilizing symbiotic relationships and assisted migration in restoration to cope with multiple stressors, and the legacy of invasive species - Markovchick, Lisa M.; Belgara-Andrew, Abril; Richard, Duncan; Deringer, Tessa; Grady, Kevin C.; Hultine, Kevin R.; Allan, Gerard J.; Whitham, Thomas G.; Querejeta, José Ignacio; Gehring, Catherine A. (Frontiers in Microbiomes, 2024)
Climate change has increased the need for forest restoration, but low planting success and limited availability of planting materials hamper these efforts. Invasive plants and their soil legacies can further reduce restoration success. Thus, strategies that optimize restoration are crucial. Assisted migration and inoculation with native microbial symbiont communities have great potential to increase restoration success. However, assisted migrants can still show reduced survival compared to local provenances depending on transfer distance. Inoculation with mycorrhizal fungi, effective if well-matched to plants and site conditions, can have neutral to negative results with poor pairings. Few studies have examined the interaction between these two strategies in realistic field environments where native plants experience the combined effects of soil legacies left by invasive plants and the drought conditions that result from a warming, drying climate. We planted two ecotypes (local climate and warmer climate) of Populus fremontii (Fremont cottonwoods), in soils with and without legacies of invasion by Tamarix spp. (tamarisk), and with and without addition of native mycorrhizal fungi and other soil biota from the warmer climate. Four main results emerged. 1) First year survival in soil legacies left behind after tamarisk invasion and removal was less than one tenth of survival in soil without a tamarisk legacy. 2) Actively restoring soil communities after tamarisk removal tripled first year cottonwood survival for both ecotypes, but only improved survival of the warmer, assisted migrant ecotype trees in year two. 3) Actively restoring soil communities in areas without a tamarisk history reduced first year survival for both ecotypes, but improved survival of the warmer, assisted migrant ecotype trees in year two. 4) By the second year, inoculated assisted migrants survived at five times the rate of inoculated trees from the local ecotype. Results emphasize the detrimental effects of soil legacies left after tamarisk invasion and removal, the efficacy of assisted migration and restoring soil communities alongside plants, and the need to thoughtfully optimize pairings between plants, fungi, and site conditions.